PLATELET TO LYMPHOCYTE RATIO IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - SIDDHARTH YASWANTH; MANOJ KUMAR PRASAD; PALAMALAI THAMILMANI PRABAKARAN; SIVA KUMAR KARUNANANDHAM (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Acute myocardial infarction (AMI) results from the total occlusion of a coronary artery, often due to thrombus formation on a complicated atherosclerotic plaque. Despite advances in reperfusion techniques, patients with AMI face poor prognosis and high early mortality rates. Inflammatory markers, such as the platelet-to-lymphocyte ratio (PLR), have shown potential in predicting poor prognosis and major adverse cardiovascular events (MACE). This study aims to evaluate the prognostic value of PLR in predicting immediate outcomes in AMI patients by examining the relationship between PLR and the Killip classification, a tool used to assess heart failure severity. Methods: This prospective observational study included 75 patients diagnosed with AMI based on clinical presentation, electrocardiographic changes, and elevated cardiac biomarkers. Ethical committee clearance and informed consent were obtained. Baseline demographic and clinical data, including smoking status, hypertension, and diabetes mellitus, were collected. The Killip classification assessed heart failure severity at admission. Blood samples were collected at admission (day 1) and at the end of the 1st week (day 7) to measure PLR values using automated hematology analyzers. Descriptive statistics summarized sociodemographic characteristics. T-tests compared PLR values between day 1 and day 7 for each Killip score, and analysis of variance assessed differences in PLR across different Killip scores. Correlation analysis evaluated the relationship between Killip scores and PLR at admission and the end of the 1st week. Results: The majority of patients were aged 40–59 years (44%) or older than 60 years (41.33%), with a predominance of male patients (70.67%). A significant number of patients were smokers (61.33%), many had hypertension (61.33%), and diabetes mellitus (57.33%). Analysis showed a significant reduction in PLR from day 1 to day 7 for all Killip scores. For instance, Killip score 1 saw a reduction from 112.34±21.09 to 93.83±15.27 (t=6.157, p<0.001). Higher Killip scores were consistently associated with higher PLR values at both time points. Correlation coefficients were 0.85 at admission and 0.82 at the end of the 1st week (p<0.001 for both), indicating a strong positive relationship. Conclusion: The study highlights the prognostic significance of PLR in AMI patients, with higher Killip scores associated with significantly higher PLR values. This consistent relationship suggests that PLR can serve as a reliable marker for early risk assessment and prognosis in AMI patients, supporting its potential utility in clinical practice. Further research is warranted to confirm these findings and explore the integration of PLR into the routine clinical management of AMI.